2019
DOI: 10.1177/0885328219896457
|View full text |Cite|
|
Sign up to set email alerts
|

Preparation of paclitaxel-folic acid functionalized gelatin grafted mesoporous hollow carbon nanospheres for enhancing antitumor effects toward liver cancer (SMMC-7721) cell lines

Abstract: Folic acid functionalized gelatin-coated mesoporous hollow carbon nanospheres (FGMCN) were synthesized and applied to enhance the antitumor curative effect of paclitaxel (PTX) for human liver cancer cell lines (SMMC-7721). PTX was loaded in FGMCN by the adsorption method and the PTX-loaded samples (PTX-FGMCN) had a drug content of 29.8 ± 1.06%. The PTX-FGMCN with a sustained release effect was characterized by X-ray diffraction and differential scanning calorimeter in order to analyze the PTX state in FGMCN. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The rapid development of nanotechnology provides new ideas for the treatment and diagnosis of cancer (Manzur et al., 2017 ; He et al., 2018 ; Dong et al., 2019 ). Currently, various nanocarriers, such as mesopore silica (He et al., 2017 ), liposomes (Eloy et al., 2020 ), carbon nanotubes (Soleyman et al., 2015 ), polymer nanoparticles (Levit et al., 2020 ), and cyclodextrin nanoparticles (Yan et al., 2019 ), have been widely incorporated with PTX to improve its solubility and targeting ability. However, these methods generally have problems including low drug loading and targeting ability.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of nanotechnology provides new ideas for the treatment and diagnosis of cancer (Manzur et al., 2017 ; He et al., 2018 ; Dong et al., 2019 ). Currently, various nanocarriers, such as mesopore silica (He et al., 2017 ), liposomes (Eloy et al., 2020 ), carbon nanotubes (Soleyman et al., 2015 ), polymer nanoparticles (Levit et al., 2020 ), and cyclodextrin nanoparticles (Yan et al., 2019 ), have been widely incorporated with PTX to improve its solubility and targeting ability. However, these methods generally have problems including low drug loading and targeting ability.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Recent articles reported that FA receptors and Tf receptors were highly expressed on the surface of SMMC-7721 cells (a typical hepatoma cell line), and Tf-targeted drug carriers could deliver the drugs to tumor sites. 21,22 However, most of the current researches concerning targeted drug delivery systems are focused only on a single target, and there are still problems of premature or accelerated drug release and difficulty in controlling time of release that, in turn, may reduce drug concentration below optimal levels at the tumor site. These problems result in undesirable drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Recent articles reported that FA receptors and Tf receptors were highly expressed on the surface of SMMC-7721 cells (a typical hepatoma cell line), and Tf-targeted drug carriers could deliver the drugs to tumor sites. 21,22…”
Section: Introductionmentioning
confidence: 99%